Kepercayaan Diri Mahasiswa Akuntansi Indonesia dalam Mengadopsi Kecerdasan Buatan (AI) - Ester Sari Lumban Tobing; Poniman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the factors that influence accounting students in Batam City in Adopting Artificial Intelligence (AI) with independent variables namely Self-Confidence, Training and Technological Infrastructure. The population in this study were accounting students in Batam City semesters 3, 5, and 7. The method used in sampling was purposive sampling technique. The sample in this study amounted to 100 people obtained using the slovin formula. Data were obtained by distributing questionnaires and using a Likert scale and then processed using SPSS Version 26. The results of this study indicate that Self-Confidence (X1) does not have a significant effect on Adopting Artificial Intelligence with a value of 0.853> 0.05, Training (X2) has a significant effect on Artificial Intelligence (AI) with a significance value of 0.000 <0.05 and Technological Infrastructure (X3) has a significant effect on Adopting Artificial Intelligence (AI) with a significance value of 0.000 <0.05. The magnitude of the influence of the independent variable with the dependent variable is 0.707 or if in percentage it is 70.7% as shown by R adjective square.